2017
DOI: 10.1158/1078-0432.ccr-16-0709
|View full text |Cite
|
Sign up to set email alerts
|

Dysregulation of EGFR Pathway in EphA2 Cell Subpopulation Significantly Associates with Poor Prognosis in Colorectal Cancer

Abstract: Purpose EphA2 receptor is involved in multiple cross-talks with other cellular networks including EGFR, FAK and VEGF pathways, with which it collaborates to stimulate cell migration, invasion and metastasis. Colorectal cancer (CRC) EphA2 overexpression has also been correlated to stem-like properties of cells and tumor malignancy. We investigated the molecular crosstalk and microRNAs modulation of the EphA2 and EGFR pathways. We also explored the role of EphA2/EGFR pathway mediators as prognostic factors or pr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
54
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(59 citation statements)
references
References 52 publications
5
54
0
Order By: Relevance
“…De Robertis et al reported that colon adenocarcinoma cells with high EphA2 expression levels isolated from the AOM/DSS mouse model showed higher levels of stem cell markers and lower levels of differentiation markers than the low-EphA2 population. 31) At the same time, ephrin-A1 was decreased in the high-EphA2 population, suggesting that the noncanonical pathway is responsible for cancer stemness properties. Miao et al reported that the Akt-EphA2 pathway is essential for glioblastoma CSC invasion and self-renewal.…”
Section: Cell Survival and Proliferationmentioning
confidence: 98%
See 3 more Smart Citations
“…De Robertis et al reported that colon adenocarcinoma cells with high EphA2 expression levels isolated from the AOM/DSS mouse model showed higher levels of stem cell markers and lower levels of differentiation markers than the low-EphA2 population. 31) At the same time, ephrin-A1 was decreased in the high-EphA2 population, suggesting that the noncanonical pathway is responsible for cancer stemness properties. Miao et al reported that the Akt-EphA2 pathway is essential for glioblastoma CSC invasion and self-renewal.…”
Section: Cell Survival and Proliferationmentioning
confidence: 98%
“…41) Many reports showed that patients with low ephrin-A1 expression had a poor prognosis, suggesting the existence of EphA2 tyrosine kinase-independent regulation. 31,42,43) Thirty-seven phosphorylation sites are identified within the intracellular domain of EphA2 in the PhosphoSitePlus database. 44) Among them, 25 phosphorylation sites are serine and threonine residues.…”
Section: Epha2 Noncanonical Signaling Transductionmentioning
confidence: 99%
See 2 more Smart Citations
“…This cellular mechanism is related to the development of colon cancer (70,71), and up regulation of EGFR has been correlated with a poor prognosis in colon cancer patients (72). Although the mechanism by which EPEC induces EGFR phosphorylation is not entirely clear, it has been showed that translocation of effectors EspF and EspZ could be associated with EGFR phosphorylation (73).…”
Section: Entero Pathogenic Escherichia Coli and Colon Cancermentioning
confidence: 99%